Formative experiences and psychological distance in the lives of contemporary environmentalists - Raja, Urooj S.; Carrico, Amanda R. (Frontiers in Psychology, 2023)
We use the term "environmentalists" to describe the people who are highly and actively engaged and involved in environmental issues like climate change. Environmentalists consistently advocate, research, or volunteer to do the work needed to address environmental challenges. The factors that drive contemporary environmentalists remain understudied. Practitioners, in particular, may need this knowledge to help environmentalists by providing them with the required resources and support to get the work done, ultimately benefiting larger society. We, therefore, ask: What formative experiences drive environmentalists on climate change and other environmental problems at present? We frame this exploration through the significant life experiences (SLE) literature, which examines people and environmental pathways. We draw on 33 interviews with environmentalists involved in environmental protection work for an average of 91 hours in the past four weeks. We find that environmentalists spoke about several formative experiences broadly consistent with what has been documented in the SLE literature. Traumatic experiences were especially influential for our sample of environmentalists. We also ask: How do feelings of perceptual/actual distance or closeness to environmental threats and climate change shape a person's decision to become an environmentalist? We draw on the psychological distance framework (PD) to answer this question. Our findings reveal that PD, especially social, plays a role in the lives of environmentalists. Study findings could help scholars and practitioners deepen their understanding of contemporary environmentalists.